Designing Model for the Development of Sustainable Small Coffee Agroindustry at the Agropolitan Area of Ijen, East Java, Indonesia - Wardhana, Danu Indra; Wibowo, Yuli; Suwasono, Sony (Department of Agro-industrial Technology, University of Brawijaya, 2023)
AbstractConsidering Indonesia is one of the world's major coffee producers, the small coffee agroindustry has much room to grow. The industry faces some challenges, including low output, limited access to the market, insufficient human resource capabilities, and improper waste treatment. This research aimed to create a model for the coffee agroindustry's growth utilizing a sustainable development concept in the form of decision support systems. The model is named AgroCoffee, which comprises six submodels: submodel of superior product selection of coffee agroindustry, submodel of social, submodel of institutional, submodel of technology, submodel of environmental, and submodel of economic. This study used several data analysis methods: exponential comparison approach, multi expert-multi criteria decision-making, interpretative structural modeling, analytical hierarchy process, and financial analysis. The model was verified in the agropolitan area of Bondowoso's Ijen highland in East Java, Indonesia. The findings revealed that the model could accurately simulate the coffee agroindustry system, which allows the model to generate recommendations for decision-makers on how to establish sustainable coffee agroindustry. Further improvements and adjustments to the model need to be conducted to develop a better model that dynamically follows the current needs and conditions to make the latest data and information obtained more accurate.Keywords: coffee agroindustry, Ijen highland agropolitan, sustainable development AbstrakIndonesia merupakan salah satu penghasil kopi terbesar di dunia sehingga agroindustri kopi rakyat berpotensi tinggi untuk dikembangkan. Permasalahan pengembangan agroindustri kopi rakyat di Indonesia yaitu: produktivitas kopi yang rendah, akses pemasaran yang terbatas, keterampilan sumber daya manusia yang rendah, dan limbah pengolahan kopi yang belum ditangani dengan baik. Penelitian ini bertujuan untuk merancang suatu model pengembangan agroindustri kopi rakyat dengan menggunakan konsep pembangunan berkelanjutan dalam bentuk sistem penunjang keputusan. Model ini diberi nama AgroCoffee, yang terdiri dari 6 submodel, yaitu submodel pemilihan produk unggulan, submodel sosial, submodel kelembagaan, submodel teknologi, submodel lingkungan, dan submodel ekonomi. Metode yang digunakan dalam analisis terdiri dari metode perbandingan eksponensial, multi expert-multi criteria decision making, interpretative structural modeling, analytical hierarchy process, dan analisis finansial. Rancangan model disimulasikan pada Kawasan Agropolitan Dataran Tinggi Ijen Kabupaten Bondowoso, Jawa Timur, Indonesia. Hasil penelitian menunjukkkan bahwa rancangan model telah mampu mensimulasikan sistem agroindustri kopi rakyat berdasarkan hasil verifikasi dan validasi pada model AgroCoffee. Oleh karena itu, model dapat diterapkan untuk memberikan rekomendasi bagi para pengambil keputusan dalam pengembangan agroindustri kopi rakyat yang berkelanjutan. Penyempurnaan dan penyesuaian model perlu dilakukan dalam rangka pengembangan sistem yang sesuai dengan kebutuhan dan kondisi saat ini sehingga data dan informasi terbaru yang diperoleh lebih akurat.Kata Kunci: agroindustri kopi, agropolitan dataran tinggi Ijen, pembangunan berkelanjutan